Winning the service game - Schneider, Benjamin, 1938-; Bowen, David Earl. (Boston, Mass. : Harvard Business School Press, 1995)
Companies that master the rules of the service game can outperform the competition. The key to winning is understanding that the customer experiences the way an organization is managed - from the treatment of the employees to the condition of the physical facilities. Winning the Service Game presents over fifty explicit rules for creating and managing a culture dedicated to delivering seamless service quality - service that, to the customer, feels like a piece of whole cloth with all the threads woven together. This groundbreaking book shows that in such an environment, employees flourish and customers experience the positive "moments of truth" that bind them to the organization.
Ch. 1. Building a Winning Service Organization by Mastering the Rules of the Game -- The Customer Tier: Achieving Customer Focus. Ch. 2. Meeting Customer Expectations. Ch. 3. Respecting Customer Needs. Ch. 4. Utilizing Customer Talents -- The Boundary Tier: Managing Personal and Nonpersonal Customer Contact. Ch. 5. Managing Personal Contact through Hiring and Training. Ch. 6. Managing Personal Contact through Reward Systems. Ch. 7. Managing Nonpersonal Contact with a Personal Touch -- The Coordination Tier: Creating a Service Culture. Ch. 8. Designing a Customer-Focused Service System. Ch. 9. Creating a Service Culture.
Includes index.
Bibliography: p. 261-283.
Keywords: Customer services -- Management; Employees -- Training of; Incentives in industry